Dynamic response of tapered optical multimode fiber coated with carbon nanotubes for ethanol sensing application - Shabaneh, Arafat Abdallah Abdelwadod; Girei, Saad Hayatu; M. Thirunavakkarasu, Punithavathi; Mahdi, Mohd Adzir; Abdul Rashid, Suraya; Paiman, Suriati; Yaacob, Mohd. Hanif (MDPI AG, 2015)
Ethanol is a highly combustible chemical universally designed for biomedical applications. In this paper, optical sensing performance of tapered multimode fiber tip coated with carbon nanotube (CNT) thin film towards aqueous ethanol with different concentrations is investigated. The tapered optical multimode fiber tip is coated with CNT using drop-casting technique and is annealed at 70 °C to enhance the binding of the nanomaterial to the silica fiber tip. The optical fiber tip and the CNT sensing layer are micro-characterized using FESEM and Raman spectroscopy techniques. When the developed sensor was exposed to different concentrations of ethanol (5% to 80%), the sensor reflectance reduced proportionally. The developed sensors showed high sensitivity, repeatability and fast responses (<55 s) towards ethanol.